Accurate phasor and frequency estimation during power system oscillations using least squares. Issue 7 (1st September 2019) - Koteswara Rao, Ayyalasomayajula Venkata; Soni, Krishan Mohan; Sinha, Sanjay Kumar; Nasiruddin, Ibraheem
Abstract : Accurate estimation of a phasor, frequency, and rate of change of frequency during changing power system condition is important to initiate precise control action for reliable power system operation. Conventional phasor estimation techniques cannot estimate the phasor accurately during dynamic conditions of power system. Furthermore, the phasor‐based frequency estimation algorithms are being affected under such conditions. In this study, both angle and amplitude modulation parameters are considered in the signal model to improve the accuracy of the phasor estimation. The method uses Taylor's series expansion to linearise the signal model and computes the signal parameters using least squares. The method first computes the phasor using estimated parameters of the signals, subsequently calculates the frequency and rate of change of frequency. The performance of the proposed method is evaluated for standard test signals. Real signals recorded in numerical relay are used to assess the performance of the proposed method. The results are compared with the available method and found that the method can supplement the existing methods used in phasor measurement units and intelligent electronic devices.